Village Funds and Village Development: The Case of West Java - Bayu Kharisma; Adhitya Wardhana; Sutyastie Soemitro Remi; Sandi Asep Ramdani (Economics Development Analysis Journal, 2025)
The Village Fund program has enabled the widespread implementation of village development initiatives that involve local communities as the subjects of development (i.e., Community Driven Development) across various countries, including Indonesia. Despite receiving substantial village funds, West Java, one of Indonesia's provinces, exhibits slow growth in the Village Development Index (IDM). This study examines the effect and impact of Village Funds on achieving the Sustainable Development Goals (SDGs), as measured by the IDM in West Java Province. The methodology employs a panel data regression with fixed effects and a Difference-in-Difference (DiD) analysis on 5,312 villages that received Village Funds between 2018 and 2023. Findings indicate that Village Funds significantly impact the IDM, primarily through infrastructure projects within the village development sector. Furthermore, the regression analysis revealed that all sectors positively and significantly influence the IDM, particularly the village development implementation sector. Conversely, the DiD analysis suggests that the alignment of Village Fund activities with the SDGs has not significantly affected IDM growth in West Java. Thus, to accelerate village development, the government must balance the prioritization of Village Funds. This balance should move beyond solely focusing on infrastructure development to encompass activities in other fields, such as village community empowerment